Influence of a tabletop scanner, used for digitization, on the determination of dose by radiochromic film (UNED Research Journal, 2023)
Introduction: The precision in determination of the dose using radiochromic films as a dosimeter is influenced by three main aspects: the dose delivery capacity of the radiation unit, the response of the film when exposed to radiation, and the capacity of the scanner to digitize the films and transform them into intensity values. This work focuses on the last aspect. Objective: To establish a methodology for the evaluation of the variability of the dose due to the repeatability of scans and the position of the film in the scanning area, under calibration conditions of radiochromic films for three different resolutions. Methods: Pieces of EBT3 radiochromic films were irradiated at 11 different dose values, which were scanned at 3 different resolutions, creating a calibration curve for each resolution. These curves are used to determine dose variations due to film position in the scan area and scan repeatability; for this purpose, we measured 5 dose values per film, for each of 9 images by resolution, with a total of 27 images. Results: In the three resolutions studied, uncertainties below 1% were found due to variation in the position of the film in the scanning area and uncertainty below 2% in the case of scan repeatability. Conclusions: The values obtained from the sources of uncertainty studied were not negligible; therefore, they must be included in the total uncertainty budget of the radiochromic film dose measurement process. Working with dose values eliminates the dependence on the resolution.
Keywords: Radiochromic film; scanner; uncertainty; film dosimetry; resolution; EBT3